Association studies of catechol-O-methyltransferase (COMT) gene with schizophrenia and response to antipsychotic treatment. (March 2009) - Gupta, Meenal; Bhatnagar, Pallav; Grover, Sandeep; Kaur, Harpreet; Baghel, Ruchi; Bhasin, Yasha; Chauhan, Chitra; Verma, Binuja; Manduva, Vallikiran; Mukherjee, Odity; Purushottam, Meera; Sharma, Abhay; et al.
Aim: We investigated the catechol- O -methyltrasferase ( COMT ) gene, which is a strong functional and positional candidate gene for schizophrenia and therapeutic response to antipsychotic medication.Materials & methods: Single-locus as well as detailed haplotype-based association analysis of the COMT gene with schizophrenia and antipsychotic treatment response was carried out using seven COMT polymorphisms in 398 schizophrenia patients and 241 healthy individuals from a homogeneous south Indian population. Further responsiveness to risperidone treatment was assessed in 117 schizophrenia patients using Clinical Global Impressions (CGI). A total of 69 patients with a CGI score of 2 or less met the criteria of good responders and 48 were patients who continued to have a score of 3 and above and were classified as poor responders to risperidone treatment.Results: The association of SNP rs4680 with schizophrenia did not remain significant after adjusting for multiple testing. Haplotype analysis showed highly significant association of seven COMT marker haplotypes with schizophrenia (CLUMP T4 p-value = 0.0001). Our results also demonstrated initial significant allelic associations of two SNPs with drug response (rs4633: χχ 2 = 4.36, p-value = 0.036, OR: 1.80, 95% CI: 1.03––3.15; and rs4680: χχ 2 = 4.02, p-value = 0.044, OR: 1.76, 95% CI: 1.01––3.06) before multiple correction. We employed two-marker sliding window analysis for haplotype association and observed a significant association of markers located between intron 1 and intron 2 (rs737865, rs6269: CLUMP T4 p-value = 0.021); and in exon 4 (rs4818, rs4680: CLUMP T4 p-value = 0.028) with drug response.Conclusion: The present study thus indicates that the interacting effects within the COMT gene polymorphisms may influence the disease status and response to risperidone in schizophrenia patients. However, the study needs to be replicated in a larger sample set for confirmation, followed by functional studies.